Assessment of Attitude and Practice of Food Hygiene among Food Handlers in Ebonyi State, Nigeria - , B. I. Ituma; , C. Onwasigwe; , E. U. Nwonwu; , B. N. Azuogu; , N. C. Eze (Archives of Current Research International, 2019)
Background: Food handlers have an important role to play in food businesses and that is to guarantee that meals served are hygienic for consumption. Conscious or inadvertent contamination of such food places consumers at risk of suffering food-borne illnesses. The aim of this study was to determine the attitude and practice of food hygiene among food handlers in Ebonyi State Nigeria. Methodology: This was a cross-sectional study in design. A multi-stage sampling technique was used to select 170 respondents. Data were collected using pre-tested interviewer-administered questionnaire and observational checklist. Statistical analyses (proportions, chi-square tests) were carried out using IBM-SPSS version 20. Results: Majority (75.9%) of the study participants were females, 84.1% were in the age range of 20-49 years. Most of the respondents (98.2%) had one form of education or the other. Only 4 (2.4%) of the restaurants had adequate physical infrastructure, availability of water supply, toilet facility, refuse and dish/hand washing facilities. Slightly above half (52.9%) of the study subjects had positive attitude toward food hygiene while only 27.6% had good practice. Only 33.5% of them wore apron, 27.1% covered their head, 18.2% did not handle money while serving food to consumers. There were however significant associations between level of education and infrastructure/environment of food premises with attitude and practice of food hygiene. Conclusion: Though there was some level of positive attitude toward food hygiene, their practice was poor. Only few restaurants had adequate infrastructure for operation. Thus, there is high risk of food contamination in the food businesses. Health education intervention programs for food handlers will help to prevent food-borne diseases/illnesses. Also regulatory agencies and government should ensure that all food premises used for preparation and sale of food to the public meet the minimum standard for operation.